Genome assembly of Hawaiian flower thrips Thrips hawaiiensis (Thysanoptera: Thripidae) - Xiaodi Hu; Houjun Tian; Yixin Chen; Yueqin Zheng; Hui Wei; Jian-Ping Chen; Chuan-Xi Zhang; Yong Chen; Yiyuan Li (Scientific Data)
Abstract The Hawaiian flower thrips, Thrips hawaiiensis, is a common flower inhabiting pest of various horticultural plant species. It damages flowers and fruits by puncturing. T. hawaiiensis shows a rapidly developed resistance to chemical control. The lack of a high-quality reference genome limits our understanding of the genetics of T. hawaiiensis. Here, we sequenced the genome of T. hawaiiensis using Oxford Nanopore sequencing technology, Illumina, and Hi-C technology, yielding a genome assembly of 287.59 Mb with scaffold N50 of 13.84 Mb. BUSCO analysis demonstrated the T. hawaiiensis genome assembly has a high-level completeness of 98.7%. In total, 18,289 protein-coding genes were annotated and 26.69% of the genome were annotated as repeats. Our study presents the first high-quality genome assembly of T. hawaiiensis and lays the foundation for further studies on thrips genetic characteristics and pest management.